Faktor-faktor yang membentuk green buying behavior tas belanja ramah lingkungan - Tristan Adi Nugraha; Yasintha Soelasih (Universitas Kristen Maranatha, 2023)
Environmental pollution that is happening is increasingly creating awareness on the consumer side. One of the causes of environmental pollution is the use of plastic bags. The use of plastic bags that are not environmentally friendly causes environmental damage. Therefore, it is necessary to change the use of inorganic plastic bags into environmentally friendly shopping bags. Changes in the use of environmentally friendly shopping bags can reduce the impact of environmental pollution. The purpose of this study was to investigate changes in green buying behavior in using eco-friendly shopping bags. Sampling used was purposive sampling and data collection using the G-form via Line and WhatsApp. The number of respondents who were taken was as many as 190 people. Hypothesis testing using the Structural Equation Model (SEM) with Smart-PLS software. The results of the study show that environmental concerns, perceived prices, and green products have an influence on green buying behavior. Meanwhile, perceived environmental responsibility has no influence on green buying behavior. The gender variable cannot moderate environmental concerns, perceived prices, green products, and perceived environmental responsibility towards green buying behavior. The results of this study indicate that environmental concern causes consumer buying behavior to change to products that are environmentally friendly. That the price perception for environmentally friendly products is felt by consumers accordingly so that their behavior changes to environmentally friendly products. Nevertheless, the variable perceived environmental responsibility cannot change consumer buying behavior. Changes in green buying behavior are not distinguished by gender. Companies engaged in the field of eco-friendly shopping bags have opportunities due to consumer awareness of using environmentally friendly shopping bags.